2 Physiotherapist's views on choosing wisely recommendations. (4th December 2019) - Zadro, Joshua; Peek, Aimie; Dodd, Rachael; McCaffery, Kirsten; Maher, Christopher
Abstract : Objectives: To evaluate physiotherapists' feedback on a draft list of Choosing Wisely recommendations and determine the percentage of physiotherapists that agreed and disagreed with each recommendation. Method: The Australian Physiotherapy Association emailed a survey to their entire membership in 2015 (∼19, 000 physiotherapists) seeking feedback on a draft list of Choosing Wisely recommendations. Participants were first asked whether the style of wording (i.e. 'Don't do X') was an acceptable method for engaging physiotherapists in discussions about evidence-based practice. Participants could answer 'Yes' or 'No' and provide feedback in a free-text field. The next five sections referred to draft Choosing Wisely recommendations and followed the same format (Yes/No for agreement and a free-text field). We performed a content analysis of free-text responses and used descriptive statistics (counts and percentages) to report agreement and disagreement with each recommendation. Results: There were 274 physiotherapists that completed the survey (∼1.4%) and 459 free-text responses across the six sections. Responses highlighted that blanket rules were inappropriate (range across sections: 13.5% to 27.9% of responses), clinical experience is more valuable than evidence (9.5% to 26.0%) and recommendations would benefit from further refining or better defining key terms (8.1% to 29.4%). There were 185 physiotherapists (67.5%) that agreed with the style of wording (i.e. 'Don't do X'). Agreement with draft recommendations ranged from 55.1% (use of electrotherapy for back pain) to 78.1% (use of validated decision rules for imaging). Conclusions: Although most physiotherapists agreed with the style of wording for Choosing Wisely recommendations and with draft recommendations, their feedback highlighted numerous issues with the recommendations. Given that only one draft recommendation was rejected, these findings could prove valuable for developing and testing strategies to increase physiotherapists' willingness to follow Choosing Wisely recommendations and so replace low-value physiotherapy with evidence-based physiotherapy.